2008
DOI: 10.1016/j.ijgo.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Preferred and actual delivery mode after a cesarean in London, UK

Abstract: In this study, VBAC was the method of delivery preferred by most women. Nonwhite women were more likely to choose VBAC over ERCS but less likely to be delivered by VBAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…Studies that evaluate these factors in concert, using regression analyses for example, provide a higher level of evidence on the independent influence of individual factors. Five prospective cohort studies, 10 -12,31,32 22 retrospective cohort studies, 13,16,19,22,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and one case-control study 23 addressed predictive factors for VBAC using regression techniques. The key factors considered by these studies can be categorized into demographic, nonclinical, past obstetric, preexisting, neonatal, and intrapartum factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that evaluate these factors in concert, using regression analyses for example, provide a higher level of evidence on the independent influence of individual factors. Five prospective cohort studies, 10 -12,31,32 22 retrospective cohort studies, 13,16,19,22,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and one case-control study 23 addressed predictive factors for VBAC using regression techniques. The key factors considered by these studies can be categorized into demographic, nonclinical, past obstetric, preexisting, neonatal, and intrapartum factors.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, nonwhite women were more likely to have trial of labor but less likely to have VBAC. 41 A retrospective multicenter study that explored possible confounders 47 noted that African-American women were younger and more likely to have premature neonates, gestational diabetes, hypertension, and to smoke than were other women in the study. AfricanAmerican women were less likely to deliver in a university hospital but had more personal delivery experience (previous vaginal or cesarean delivery) than did women of other races.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, it is suggested that many women with a previous CS prefer a vaginal birth for the next birth. For example, an analysis of the records of more than 200 women at a London hospital demonstrated that, VBAC was the method of delivery preferred by most women although only 37.8% of those who chose it were delivered by it (Selo-Ojeme et al 2008). In Australia, a qualitative study showed that women held strong views about the importance of working with their bodies to achieve a vaginal birth after a prior caesarean section (Fenwick et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…18 Many factors, including site of delivery (rural vs urban), type of hospital (teaching vs community), history of prior vaginal delivery (including prior VBAC), and race/ethnicity (black and other minorities vs white), had been identified to modify TOLAC rates. 18,2125 The incidence of VBAC among people who had TOLAC is approximately 74% in the United States. 18 …”
Section: Practice Of Vbacmentioning
confidence: 99%